Peran Pengetahuan Investasi, Literasi Keuangan Dan Motivasi Investasi Terhadap Minat Mahasiswa Dalam Berinvestasi Di Pasar Modal - Made Surya Pramana; I Putu Iwan Pramana Putra; Ida Ayu Agung Idawati (Warmadewa Management and Business Journal (WMBJ), 2026)
Investment is a crucial financial instrument for long-term financial planning, especially for students as the younger generation who will face various economic challenges in the future. A lack of understanding and awareness regarding investment can impact student engagement in capital market activities. The purpose of this study was to analyze the influence of investment knowledge, financial literacy, and investment motivation on investment interest in the capital market among students at the Faculty of Economics and Business, Warmadewa University in Denpasar City, Bali Province. The sample consisted of 100 students selected using purposive sampling. Data analysis in this study used multiple linear regression analysis with SPSS version 27. The results showed that investment knowledge, financial literacy, and investment motivation simultaneously had a significant positive effect on students' investment interest in the capital market. Investment knowledge, financial literacy, and investment motivation also partially had a positive and significant effect on students' investment interest in the capital market.